智歯周囲炎から溶血発作を生じたG6PD異常症の1例 - 傳田, 祐也; 野池, 淳一; 五島, 秀樹; 清水, 武; 川原, 理絵; 横林, 敏夫 (日本口腔外科学会雑誌, 2012)
Glucose-6-phosphate dehydrogenase （G6PD） plays an important role in the in vivo consumption of reactive oxygen species. One must exercise caution during the treatment and selection of medicines for any illness in patients with abnormality of this enzyme, because pain and stress caused by surgery and anesthesia combined with the effects of various drugs can cause hemolysis. We describe a patient with G6PD deficiency who had a hemolytic episode caused by pericoronitis of the mandibular third molar. A 32-year-old man had a hemolytic episode after dental treatment, which comprised resin fillings, and was hospitalized because of apparent general malaise. We decided to extract the affected third molar and complete the resin fillings during the course of hospitalization. Red blood cells and hemoglobin reached their lowest levels one week after the resin filling was done, after which recovery became evident. Moreover, the frequency of hemolytic episodes decreased after extraction of the affected third molar. We considered the mandibular third molar pericoronitis and pulpitis as the possible inflammatory causes of the patient’s hemolytic episodes, while the resin filling may have been a drug-related cause. There is also the possibility that oral inflammation caused the hemolytic episodes. Our findings suggest the importance of improved dental hygiene in patients with G6PD deficiency to prevent the occurrence of hemolytic episodes.